PENGARUH KELENGKAPAN SARANA PRASARANA BELAJAR DAN METODE PEMBELAJARAN TERHADAP HASIL BELAJAR MAHASISWA PROGRAM STUDI ADMINISTRASI PERKANTORAN - Wisang Yanu Ardani (JIKAP (Jurnal Informasi dan Komunikasi Administrasi Perkantoran), 2019)
The current study aimed to examine (1) the effect of learning facility on student's learning outcome in archive subject; (2) the effect of lecturer's learning method on student's learning outcome in archive subject; and (3) the interplay of facility and lecturer's learning method on student's learning outcome. The population of the study was the sixth-semester students class A and B of Office Administration Education department who had passed archive subject. They were selected using saturated. The present research employed correlational design. The data were collected using facility questionnaire and learning method questionnaire. The data regarding learning outcome were gathered from the result of the midterm examination. The data were analyzed using multiple regression analysis and then followed by Kolmogorov-Smirnov normality test with 0.5 significance level. The results of the study are as follow. (1) the study found that learning method significantly affects learning outcome (rcount 0,468 > rtable 0,254). (2) the study found that learning facility significantly affects learning outcome (rcount 0,458 > rtable 0,254). (3) the study found that facility and learning method affect learning outcome (Fcount 17,746 > Ftable 3,17). The R2 value was 0.384. This indicated that learning facility and method simultaneously affect learning outcome by 38.4%, while the rest of it is addressed by other variables outside the study.